Pengaruh ESG Disclosure Terhadap Kinerja Keuangan Perusahaan: Sustainability Committee Sebagai Pemoderasi - Silviani, Amanda Agnes; Kamaliah, Kamaliah; Wiguna, Meilda (AKTSAR: Jurnal Akuntansi Syariah, 2024)
Environmental, Social, and Governance (ESG) disclosure has become increasingly important in recent years as investors become more aware of the company's impact on society and the environment. Sustainability committees play a crucial role in this process as they are responsible for ensuring that a company's ESG practices are transparent and aligned with its overall strategy. This research examines the relationship between ESG disclosure and company financial performance, with the Sustainability Committee as a moderating variable.  The study focuses on 205 non-financial public companies listed on the Indonesia Stock Exchange from 2019 to 2023, using panel data analysis with STATA version 17. The findings reveal a positive correlation between ESG disclosure and financial performance, where higher levels of ESG transparency lead to better financial results. The Sustainability Committee strengthens this relationship, pointing out that its presence significantly affects the impact of ESG disclosures on financial performance.